THE EFFECT OF WORKLOAD, WORK FACILITIES, AND WORK ENVIRONMENT BASED ON THE WORK OF PEKALONGAN CITY TRANSPORTATION SERVICE EMPLOYEES - Winda Lastuti; Artha Febriana (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2022)
AbstractThe success of a government agency in achieving its goals cannot be separated from the participation of employees. The importance of the existence of human resources encourages government agencies to pay attention to matters relating to employee satisfaction. This study aims to determine the effect of workload, work facilities, and work environment on employee job satisfaction. The population in this study wereall employees as many as 109 respondents. The sampling technique used is the census method. The method of data analysis was carried out using multiple linear regression. The results showed that (1) workload had a significant negative effect on employee job satisfaction; (2) work facilities have a significant positive effect on employee job satisfaction; (3) the work environment has a significant positive effect on employee job satisfaction.Keywords: Workload; Work Facilities; Work Environment; Job SatisfactionAbstrakKeberhasilan suatu instansi pemerintah dalam mencapai tujuan tidak bisa lepas dari peran serta pegawai. Pentingnya keberadaan sumber daya manusia ini mendorong instansi pemerintah untuk memperhatikan hal-hal yang berkaitan dengan kepuasan pegawai. Penelitian ini bertujuan untuk mengetahui pengaruh beban kerja, fasilitas kerja, dan lingkungan kerja terhadap kepuasan kerja pegawai. Populasi dalam penelitian ini adalah seluruh pegawai sebanyak 109 responden. Teknik pengambilan sampel yang dipakai yakni metode sensus. Metode analisis data dilakukan dengan menggunakan regresi linear berganda. Hasil penelitian menunjukkan bahwa (1) beban kerja berpengaruh negatif signifikan terhadap kepuasan kerja pegawai; (2) fasilitas kerja berpengaruh positif signifikan terhadap kepuasan kerja pegawai; (3) lingkungan kerja berpengaruh positif signifikan terhadap kepuasan kerja pegawai.Kata Kunci: Beban Kerja; Fasilitas Kerja; Lingkungan Kerja; Kepuasan Kerja